Um ambiente computacional para a arquitetura pedagógica debate de teses - Fernandes Junior, José Ilton Chiaradia (2015)
Although the use Debate of Thesis pedagogical architecture is desirable, its use is not trivial for the teacher who coordinates the debate. Our research seeks to find contributions to such coordination, reaching the designation task of reviewers and reuse of theses its focus by offering a solution that aims to enhance its use in order to contribute to this tool. The theses are important tools in the debate, as well as propose their theme, seek to place participants in situations that promote the clash of ideas and therefore the acquisition of knowledge, and interesting to create a database of theses for reference and reuse. For this exchange to take place it is necessary to determine the couple who acted in the arguments of shock, work coordinator that can be brokered by a less dependent on their actions system. In this paper we propose a conceptual model, and a proposal to implement a prototype for Educational Architecture Thesis Debate that takes into account the requirements set out in its conceptual proposal not only includes the features. We also present a working prototype that besides the basic functionality includes the features that have been studying the objects that originated the dissertation.